Dose optimisation in paediatric radiography – Using regression models to investigate the relative impact of acquisition factors on image quality and radiation dose. (December 2019) - Mohammed Ali, Ali; Hogg, Peter; England, Andrew
Highlights: Dose optimised technique reported for paediatric pelvis radiography. SID has the lowest impact on IQ and radiation dose. Filtration had a greater effect on radiation dose than kVp. kVp had higher impact on IQ than additional filtration. Impact ratios were higher for IQ than radiation dose. Abstract: Objective: To investigate the optimum pelvis X-ray acquisition factors for a 10-year-old child. Secondly, to evaluate the impact of each acquisition factor on image quality (IQ) and radiation dose. Method: Images were acquired using a pelvis phantom and a range of acquisition parameters; e.g. tube potential, additional filtration and source-to-image distance (SID). Automatic exposure control (AEC) was used with two orientations (head towards/away from two outer chambers) and three different chamber selections. Visual IQ was evaluated using relative and absolute-VGA methods. Radiation doses were measured by placing a dosimeter on the anterior surface of the phantom. Regression analysis was used to determine optimum parameters. Results: The optimised technique (178.8 µGy), with diagnostic IQ, was with 89kVp, 130 cm SID and with 1 mm Al + 0.1 mm Cu filtration. This technique was with the head towards the two outer AEC chambers. Regression analysis showed that SID had the lowest impact on IQ (β = 0.002 95% CI −0.001 to 0.005) and dose (β = −0.96 95% CI −0.40 to −1.53). The impact of filtration on dose (β = −76.24 95% CI −86.76 to −85.72) was higher than tube potential (β = −13.44 95% CI −14.34 to −12.53). The following impact ratios were higher on IQ than radiation dose: filtration/kVp; 11.28 times, filtration/SID; 7.01 times and kVp/SID; 0.62 times. Conclusion: Optimised parameters were identified as 89 kVp, 130 cm SID and with 1 mm Al + 0.1 mm Cu additional filtration. Regression analysis demonstrated that filtration and tube potential had the greatest effect on radiation dose and IQ, respectively.